Impact of Fasting as Riyadhah on Self-Control Among Islamic Boarding School Students in Yogyakarta - Siti Fauziyah (Millah: Journal of Religious Studies, 2021)
Most Islamic boarding school (pesantren) students believe that learning is not enough for them to benefit from their knowledge. Riyadhah, which involve fasting for a minimum of 3 years, is believed to be a common practice among students. During riyadhah, they train themselves to refrain from eating, drinking, anger, and things that break the fasting. It is vital to analyze the impact of these practices on students. This study examines the impact of fasting on self-control using a case study approach with 3 informants who practised riyadhah for years. The results showed that fasting trains students to control themselves and their emotions, giving meaning to gratitude and patience in life. Furthermore, riyadhah fasting increased emotional intelligence and self-maturity.